Effect of Political Stability on International Tourism in Kenya - Gikonyo, James (International Journal of Modern Hospitality and Tourism, 2024)
Purpose: The aim of the study was to analyze the effect of political stability on international tourism in Kenya. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Political stability is essential for international tourism in Kenya, as stability fosters a sense of safety that attracts foreign visitors. During peaceful periods, Kenya sees growth in tourist arrivals and revenue, while political unrest, such as the post-election violence in 2007-2008, results in sharp declines as safety concerns deter tourists. Tourism in Kenya is highly sensitive to political fluctuations, with even minor instability affecting tourist perceptions. To sustain and grow its tourism sector, Kenya must prioritize political stability through effective governance, peaceful elections, and strong conflict resolution strategies, which will help build a resilient tourism industry. Unique Contribution to Theory, Practice and Policy: Social conflict theory, political economy theory & the institutional theory may be used to anchor future studies on the effect of political stability on international tourism in Kenya. Implementing robust governance practices, such as transparency, accountability, and anti-corruption measures, will enhance the overall tourist experience and foster trust among potential visitors. Formulating policies that promote good governance and strengthen institutions will create a conducive environment for political stability.